Sistem Analisis Prediksi Penjualan Vitamin di Apotek Menggunakan Metode Trend Moment - Rahmadona Nasrun Nasution (JURIKOM (Jurnal Riset Komputer), 2022)
The coronavirus pandemic has also paralyzed the world economy, including Indonesia, in several sectors such as tourism and MSMEs. However, other sectors such as health and food remained stable and even experienced a surge in sales, especially sales of vitamin drugs at pharmacy outlets. One of them is Apotek Manjur Marendal, which experienced an increase in sales of medicines such as vitamins during the pandemic. To meet consumer demand and to process the right stock of vitamin drugs so that there is no loss, a prediction technique for vitamin drug sales is needed with data mining. With data mining techniques, Apotek Manjur Marendal can predict sales during the pandemic, so that profits and losses and stock of vitamin drug sales can be controlled. Data mining techniques require methods to make the calculations more complex. Several methods have been created by several inventors, one of which is the Trend Moment method. Based on the prediction results of vitamin drug sales using the Trend Moment method on sales data for 1 year during the 2021 pandemic period, it was obtained prediction results for the next 1 year in the 2022 period that sales of vitamin drugs such as Becom C, Enervon C, Ester C, Hevit C and Vitalong C stable with sales ±5000vitamin drugs sold in total, while the prediction accuracy reached the highest accuracy > 90% and the lowest accuracy 64%.